Mutation of Bacillus firmus OF4 to duramycin resistance results in substantial replacement of membrane lipid phosphatidylethanolamine by its plasmalogen form. - Clejan, S (1989)
Mutant strains of alkalophilic Bacillus firmus OF4 that were selected for resistance to duramycin had greatly reduced levels of membrane diacylphosphatidylethanolamine, as had been found in studies of such mutants of Bacillus subtilis. In the B. firmus strains, however, substantial levels of plasmenylethanolamine were found. This is an unusual membrane component for an aerobic eubacterium, but the presence of trace amounts even in the wild type was confirmed in experiments with 32Pi-labeled growth medium. The membrane lipid composition of the duramycin-resistant strains had several other changes that also left alkalophilic growth unimpaired.